Syntheses and characterization of o-carboranes containing fused exo-polyhedral di- and triboraheterocycles - Nie, Yong; Miao, Jinling; Wadepohl, Hubert; Pritzkow, Hans; Oeser, Thomas; Siebert, Walter (Zeitschrift für anorganische und allgemeine Chemie, 2013)
Reaction of dilithio-o-carborane Li2C2B10H10 (generated in situ from o-carborane 1 and butyllithium) with the 1, 2-diborylbenzene derivative 1, 2-C6H4(iPr2NBCl)2 yielded the o-carborane compound 3 having the fused exo-polyhedral C2B2C2 heterocycle. The analogous reactions with 1, 1-bis(dimethylaminochloroboryl)ethane and with 1, 3-dichloro-1, 2,3-tris(dimethylamino)triborane(5) afforded the o-carborane compounds 5 and 7 containing the fused exo-polyhedral five-membered C2B2C and C2B3 rings, respectively. Attempts to use 1, 2-dichloro-1, 2-bis(dimethylamino)diborane(4) for the synthesis of the o-carborane compound 10 with a fused exo-polyhedral C2B2 ring instead led to the diborane(4)yl-o-carborane species 9c and 9d (the latter in trace amount), which contain a diborane(4)yl moiety bonded to the o-carborane. The molecular compositions of the new o-carborane derivatives follow from NMR spectroscopic and mass spectrometric data as well as from X-ray diffraction analyses of 3, 7 and 9c. The structures exhibit weak intramolecular C-H···H-B hydrogen-hydrogen interactions.